The Indies Chinese and the Sarekat lslam: AnAccount of the Anti-Chinese Riots in ColonialIndonesia - Azyumardi Azra (Studia Islamika, 1994)
Educational policy towards the native Dutch 19th century has been a lot of encouraging the emergence of the seeds of nationalism (proto-nationalism). This policy allows certain native circles to get the Dutch education. Although the number is very small, the role of native Dutch school graduates is very important. They became the backbone of the national people's attitudes develop bumiputera.DOI: 10.15408/sdi.v1i1.865